1988
DOI: 10.1111/j.1365-2125.1988.tb03312.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the effects of epoprostenol on effective pulmonary blood flow in normal volunteers.

Abstract: 1 Epoprostenol (prostacyclin) has been widely used as a vasodilator, but its effects on cardiac output are controversial and the time course of its effects little studied.2 We report its cardiovascular effects in doses of 5 and 10 ng kg-' min-' in six healthy volunteers. 3 Each of the two doses caused a mean 20% rise in effective pulmonary blood flow and a 15% rise in heart rate. These effects appeared to reach a maximum within 10 min of starting or increasing the rate of infusion, with no evidence of a reboun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The heart rate was recorded every 15 s on a single channel ECG machine, and measured from the R-R interval. Since we had previously shown that the measurement of Qp.eff significantly affects heart rate (Bush et al, 1988), we took the mean of the six measurements from 15 to 90 s in the cycle illustrated in Figure 1. All other heart rate data were discarded.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heart rate was recorded every 15 s on a single channel ECG machine, and measured from the R-R interval. Since we had previously shown that the measurement of Qp.eff significantly affects heart rate (Bush et al, 1988), we took the mean of the six measurements from 15 to 90 s in the cycle illustrated in Figure 1. All other heart rate data were discarded.…”
Section: Measurementsmentioning
confidence: 99%
“…It was measured from the time constant of the fall in the partial pressure of freon-22. A fixed time interval was used for the calculation (12-24 s from the start of the manoeuvre for all subjects), because a previous study had shown that this yielded more reproducible results than selecting a linear portion by eye (Bush et al, 1988), using this method. The mean coefficient of variation of Qp.eff within a study is 5.5% (Bush et al, 1988), and between studies is 6.5% (Waller, 1982).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean within study coefficient of variation (100 x s.d./mean) of EPBF has been shown to be 5.5% (Bush et al, 1988). The between study mean coefficient of variation of EPBF has been shown to be 6.5% (Waller, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…EPBF was measured from the time constant of the fall in the partial pressure of freon-22 between a previously fixed time interval (usually 10-20 s from the start of the manoeuvre), because a previous study had shown that this yielded more reproducible results than selecting a linear portion by eye (Bush et al, 1988). The mean within study coefficient of variation (100 x s.d./mean) of EPBF has been shown to be 5.5% (Bush et al, 1988).…”
Section: Methodsmentioning
confidence: 99%